Are We There Yet? A Progress Report from Three Turkish University Pioneers in Distance Education and E-Learning - Latchem, Colin; Simsek, Nurettin; Balta, Ozlem Cakir; Torkul, Orhan; Cedimoglu, I. Hakkı; Altunkopru, Alpaslan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The international literature provides little in-depth analysis of distance education and e-learning activities, achievements, and challenges in Turkish higher education other than the country’s mega-university, Anadolu. This paper examines the development of, and lessons to be learned from, such undertakings by three pioneers, two regular state universities, Ankara University and Sakarya University, and the private, non-profit Turkish-Kazakhstan Ahmet Yesevi University. Drawing on the collective experience of the authors, the paper reaches some overall conclusions about embarking on distance education and e-learning, which may apply in other Turkish universities and similar economies.